Developing a community-based nursing and midwifery career pathway - A narrative systematic review - Harvey C; Hegney D; Sobolewska A; Chamberlain D; Wood E; Wirihana L; Mclellan S; Hendricks J; Wake T (PLOS, 2019)
INTRODUCTION: Community nursing and midwifery is changing in response to a shift in care from hospital to home, brought about by increasing costs to care because of an aging population and increasing chronicity. Until now, community nursing positions and scope of practice has been dependent on service focus and location, which has led to the role being unclearly defined. Lack of appeal for a career in community practice and a looming workforce shortage necessitates a review into how community nursing and midwifery transition to practice is supported. METHODS: This review sought to identify, assess and summarize available evidence relating to transitioning into community nursing and midwifery practice as a speciality. A systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses approach. A narrative synthesis was then undertaken on papers that examined community nursing and midwifery pathway perspectives which define, and enable or inhibit a contemporary pathway. Thematic analysis used a theoretical framework developed for early career and rapid transition to nursing specialty practice. RESULTS: There is a paucity of research that identifies community nursing and midwifery as a discreet scope of practice. Twelve papers were eventually included in the review. Verbatim findings were extracted from the papers and clustered into categories based on the chosen theoretical framework. Major themes were 'the self' (professional and personal); 'transition processes'; and, a 'sense of belonging'. Sub themes included narrative identifying inhibitors and enablers in each theme. DISCUSSION: No definition of community practice or pathway was identified in nursing, although midwifery was clearly defined. Community nursing practice was described as generalist in nature although specialist knowledge is required. Being part of the community in the professional sense and personal sense was considered important. The importance of transition was identified where pre-entry exposure to community practice was seen as important. Stages in transition to practice were recognised as pre-entry; incomer; insider; and, a sense of belonging. The process of transition should be planned and individualised acknowledging past experience whilst acknowledging the specialist nature of community-based practice.
Copyright: © 2019 Harvey et al.
Keywords: Clinical Competence; Community Health Nursing; Community Medicine; Humans; Midwifery; Narration; Nurse's Role